1997
DOI: 10.1002/bies.950190104
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mutation: A general phenomenon or special case?

Abstract: A recent article by Galitski and Roth characterizes adaptive reversion of chromosomal lac- mutations in Salmonella typhimurium LT2. Using a classical genetic approach they show that adaptive reversion, as characterized by the appearance of late revertant colonies, is an exception rather than a general phenomenon for reversion of nonsense, missense, frameshift and insertion mutations. For certain mutations, however, the number of late revertants exceeds the predicted number. These excess revertants suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The rapidity of takeover of chemostat populations by fitter bacteria is also well known (Helling et al, 1987), but the number and type of mutations in these evolved bacteria has never been defined. Also, the relationship of DNA changes under nutrient limitation to the contentious 'directed' or 'adaptive' mutations observed in agar plate selections of Cairns et al (1988), Foster (1993), Sniegowski and Lenski (1995) and Benson (1997) is also unknown. In this and the accompanying study (Notley-McRobb and Ferenci, 1999), we identify some of the most commonly found mutations in glucose-limited populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapidity of takeover of chemostat populations by fitter bacteria is also well known (Helling et al, 1987), but the number and type of mutations in these evolved bacteria has never been defined. Also, the relationship of DNA changes under nutrient limitation to the contentious 'directed' or 'adaptive' mutations observed in agar plate selections of Cairns et al (1988), Foster (1993), Sniegowski and Lenski (1995) and Benson (1997) is also unknown. In this and the accompanying study (Notley-McRobb and Ferenci, 1999), we identify some of the most commonly found mutations in glucose-limited populations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the relationship of DNA changes under nutrient limitation to the contentious ‘directed’ or ‘adaptive’ mutations observed in agar plate selections of Cairns et al . (1988), Foster (1993), Sniegowski and Lenski (1995) and Benson (1997) is also unknown. In this and the accompanying study (Notley‐McRobb and Ferenci, 1999), we identify some of the most commonly found mutations in glucose‐limited populations.…”
Section: Introductionmentioning
confidence: 99%
“…Other workers can and do use it in a variety of other senses. Our discussion, however, concerns Lamarckian inheritance as a biological phenomenon (for a sampling of the recent literature on Lamarckian forms of inheritance, see Andersson et al 1998;Benson 1997;Jablonka & Lamb 1995;Lenski & Mittler 1993;MacPhee & Ambrose 1996;Peck & Eyre-Walker 1998;Rosenberg et al 1995).…”
Section: Variationmentioning
confidence: 99%
“…Gershenson [99] used the terminology directed mutations for these phenomena, but he called them non-adaptive because the mutations were of a certain kind, but unfavorable as such. Fifty years later, a revival of this terminology happened after Cairns and Foster [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Specificity Of Mutationsmentioning
confidence: 99%
“…Davis [10] contributed in the discussion with a non-Lamarckian mechanism for substrate-induced mutations and by mentioning the implications of this controversial concept of environmentally induced mutations for the speed of evolution. The discussion [11][12][13][14][15][16] and generation of new data continue until today [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%